Guidewire-Related Complications during Central Venous Catheter Placement: A Case Report and Review of the Literature - Faisal A. Khasawneh; Roger D. Smalligan (Case Reports in Critical Care)
Seldinger's technique is widely used to place central venous and arterial catheters and is generally considered safe. The technique does have multiple potential risks. Guidewire-related complications are rare but potentially serious. We describe a case of a lost guidewire during central venous catheter insertion followed by a review of the literature of this topic. Measures which can be taken to prevent such complications are explained in detail as well as recommended steps to remedy errors should they occur.